Pathological changes in the lumbar intervertebral discs among professional field hockey players - Ogurkowska, M.; Kawalek, K. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Acute injuries or chronic overloading can be the cause of lower back pain. Long-term, highly-specialized training can cause the musculoskeletal system to become overloaded. Field hockey is an example of a sport which, due to the players` non-ergonomic positions, can lead to degenerative changes in the lumbar spine. METHODS: The aim of this study was to evaluate the condition of the lumbar spine among 20 male players of the Polish national team in field hockey, aged between 24 and 35 years of age, and having trained in the discipline of field hockey for a period of between 14 and 26 years. CT scans were used to determine the height of vertebrae and intervertebral discs. RESULTS: The study showed a number of differences in lumbar discs and vertebrae that are typical results of overloading. A significant decrease in disc height was observed, as well as changes in the shape of the vertebrae, which acquired a wedge shape. Analysis of the Relative Height Coefficient showed that these changes are both severe and exacerbated by years of training. CONCLUSIONS: This research proves that field hockey as an active sport strongly affects the lumbar section of the spine. As a therapeutic procedure, a special regime including muscle stretching and lumbar spine stabilization exercises should be created for both advanced and beginner players.